Alumina Extraction From Low-Grade Diasporic Bauxite By Pyro-Hydro Metallurgical Process - Ahmet Alp; Ali Osman Aydın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2000)

(untitled)
Diasporic bauxite samples obtained from Isparta-Yalvaç region were crashed and sieved with a 100 mm sieve. After determining the composition by chemical analysis, grain size distribution of the samples were determined. Then the characterization of the sample was recorded by static and dynamic thermal analysis and XRD studies. Bauxite samples added CaO and Na2CO3 were calcined at 900 ºC. Alumina extraction studies were performed for 20, 40, 60, 80 minutes of calcination time and 15, 30, 45, 60 minutes of leach time and 25, 50, 75, 100 ºC of leach temperature. It was found that the maximum leach yield (85.04 %) was obtained at 60 minutes of calcination time and 15 minutes of leach time and 50 ºC of leach temperature. These results demonstrated that the optimum conditions for dissolving to this type of iron-rich low grade diasporic bauxite minerals at low-temperature and alkaline concentration were determined.